Tax Avoidance Behavior: The Contribution of Gender Diversity, Education Level, and Firm Size Moderation - Hadi, Zufly Amrullah; Sudarto, Triadi Agung; Sidharta, Eka Ananta (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Taxes are the most significant source of state revenue. From a company's perspective, taxes can also be considered the largest expense. Therefore, top management strives to reduce the company's tax liability. This study aims to confirm the reliability of attribution theory as an approach to explain the impact of gender diversity and education levels on tax avoidance, as well as the role of company size in moderating the relationship model. In this quantitative study, energy and basic material companies listed on the Indonesia Stock Exchange from 2020 to 2023 were the population and sample of the study. The researcher used the Moderated Regression Analysis model to test time series data using SMART-PLS software. Time series data was used because it was considered capable of providing a more accurate view over time, thereby facilitating the researchers' analysis. Based on the first finding, gender diversity had a negative effect on tax avoidance; the second finding was that education level had a positive effect on tax avoidance; the third finding was that company size was able to moderate the relationship between the independent variables and the dependent variable. These findings support all hypotheses proposed by the researcher. The research results support attribution theory in explaining empirical evidence regarding the impact of gender diversity and education level on tax avoidance, as well as the role of company size.